Democracy as simulacrum: incredulity towards the metanarrative of emancipation in Ian McEwan’s saturday - Seyed Javad Habibi (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Laying bare simulacrum–oriented aspect of the western democracy in the contemporary world within almost a single day—15 September 2003—is what McEwan highlights in his novel Saturday (2005). To substantiate this hypothesis, Lyotard’s definition of postmodernism especially his notion of incredulity towards metanarrative of emancipation is taken as the theoretical backbone to animadvert the contemporary assumption of democracy. Dramatizing the terrorized and terrorizing life of Henry Perowne, Saturday reveals the real blank face of democracy, the fact that democracy in its postmodern veil has lost its traditional essence and is shrank to hollow mask which has risen itself to be a simulacrum. The concluding section of this study discusses that the ramification of this dominating “simulative democracy” is nothing but hegemonic control, a phenomenon, which according to Baudrillard, begets terrorism.